A case study on the assessment of response modification coefficient and earthquake-induced collapse potential of a high-rise setback tower. Issue 9 (2nd September 2017) - Kildashti, Kamyar; Mirghaderi, Rasoul
Abstract: This paper evaluates response modification coefficient ( R -factor) and collapse potential of a high-rise tower with setback irregularity under spectral-matched ground motion records. The tower is comprised of two legs with three distinct lateral bearing systems in elevation and curved configuration in plan. Furthermore, it has a setback in elevation, recognised by inclined columns joining two legs of the tower in uppermost stories. These characteristics cause the tower to classify as a complex irregular structure in which using code-based R -factor is highly dubious. In this paper, initially, an analytical model of the tower was subjected to a suite of ground motions to estimate collapse potential and equivalent R -factor in accordance with FEMA P695. Alternatively, structural performance parameters including inter-storey drift ratios, residual drift ratios and plastic hinge rotations were compared to TBI acceptance criteria. To achieve consistent safety margin against collapse, the value of 8 was suitable for R -factor. In spite of satisfactory threshold in accordance with FEMA P695 and TBI guidelines, for a structure with irregular configuration and multiple bearing system, damages can be localised close to zones of change in lateral bearing system that may lead to partial collapse.